Simplified Whittle estimators for spectral parameters of stationary linear models with tapered data - Ginovyan, M. S. (Հայաստանի ԳԱԱ)
The paper is concerned with the statistical estimation of the spectral parameters of stationary models with tapered data. As estimators of the unknown parameters we consider the tapered Whittle estimator and the simplified tapered Whittle estimators. We show that under broad regularity conditions on the spectral density of the model these estimators are asymptotically statistically equivalent, in the sense that these estimators possess the same asymptotic properties. The processes considered will be discrete-time and continuous-time Gaussian, linear or L´evy-driven linear processes with memory.
Keywords: Mathematics